The Crisis and Miss Emily's Perceptions - Leruth, Luc.; Nicolas, Pierre (Washington, D.C. : International Monetary Fund, 2010)
The Crisis and Miss Emily's Perceptions draws an analogy between the theme and the characters in Faulkner's short story "A Rose for Emily" and the global financial crisis. In Faulkner's story, all the characters try to deny realities, thus allowing an unstable situation to last longer than it should have. The paper briefly reviews the literature on perception biases and argues that all economic actors have, to some degree, been refusing to face realities, which helped the crisis to unfold.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet